A Conceptual Model for Revitalizing University Waqf through Strategic Partnerships with MSMEs - Syahirul Alim, Ahmad; Prasetyo, Eko; Warijan, Warijan (Jurnal Manajemen, 2026)
This paper proposes a conceptual model for revitalizing university waqf through a Sustainable University Endowment (SUE) framework. It addresses the escalating financial challenges faced by higher education institutions in Indonesia, which are characterized by a low gross enrollment ratio and an unsustainable reliance on tuition fees. Employing a conceptual mapping methodology, this study systematically identifies, organizes, and synthesizes key constructs from classical waqf practices, contemporary waqf innovations, and higher education finance literature. Drawing on the historical financial autonomy of Al-Azhar University and recent developments in Islamic social finance, the SUE model strategically integrates Micro, Small, and Medium Enterprises (MSMEs) to foster a self-sustaining financing ecosystem. The model’s core contribution lies in its structured mechanisms for leveraging university waqf assets to empower MSMEs through fair rental schemes, business incubators, Shariah-compliant financing, and expert mentorship. This integrated strategy aims to accomplish two key goals: broadening university revenue streams to lessen dependence on tuition fees and improve access to higher education, while at the same time promoting local economic development and strengthening community resilience through the empowerment of MSMEs. The SUE model thus offers a practical blueprint for Indonesian universities to achieve long-term financial sustainability and contribute significantly to national development goals within an Islamic economic framework